miR-203a-3p regulates the cellular processes of esophageal cancer cells via targeting CtBP2 - Jiang, Maorong; Shi, Hui; Xu, Yunzhao; Bai, Wen; Wang, Peiwen; Ju, Qianqian (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: MicroRNAs (miRNA) (small noncoding RNAs) are vital modulators of gene expression by mRNA degradation and translational silencing. However, the definite mechanism and character of miR-203a-3p in regulating esophageal carcinoma cells remain unexplained. Here we further investigate the effect and the latent target gene of miR-203a-3p on the progression of esophageal squamous cell cancer (ESCC) tissues and cells. Methods: The expressions of miR-203a-3p in ESCC tissues and peri-neoplastic tissues were further measured by RT-quantitative-PCR (RT-qPCR). Luciferase assay was applied to confirm that C-terminal- binding protein 2 (CtBP2) was the potential target gene of miR-203a-3p. miRNA mimic was transfected into ECA109 cells to up-regulate the miR-203a-3p expression, and its and CtBP2 expression were tested using RT-qPCR and Western blot. In vitro, MTT, transwell, wound healing, TUNEL and flow cytometry (FCM) assay were used to explore the role of miR-203a-3p on the cellular processes of ECA109 cells via targeting CtBP2. Furthermore, we designed rescue experiments by using CtBP2 stable over-expression ECA109 cells. Results: We found the miR-203a-3p expressions in ESCC tissues and cells were significantly raised. miR-203a-3p negatively regulated the CtBP2 expression, and caused to inhibiting proliferation, migration and invasion, and promoting apoptosis in ECA109 cell. In addition, proteins involved in epithelial- mesenchymal transition (EMT) were measured by Western blot in ECA109 cells. miR-203a-3p enhanced the E-cadherin and β-catenin expression, while reduced vimentin expression in ECA109 cells. In vivo, Xenograft tumor model demonstrated that tumor volume in miR-203a-3p agomir group was remarkably decreased. Conclusions: miR-203a-3p plays a vital role in the metastasis of ESCC cell by targeting CtBP2, and offers a promising therapeutic target for ESCC treatment.